The Acceptance of the English Language Learning Mobile Application Hello English Across Gender and Experience Differences - Putra, I Dewa Gede Rat Dwiyana; Saukah, Ali; Basthomi, Yazid; Irawati, Enny (International Journal of Emerging Technologies in Learning (iJET), 2020)
Abstract— This study is aimed at investigating the relationship between stu-dents’ perceived effect (PE) and their intention to use (IU) one of the English language learning mobile applications which is called Hello English, and also the differences of students’ PE and IU based on gender and experience. There are 24 male and 73 female students who completed the online survey which was admin-istered to several universities in Indonesia. The result of a bivariate correlation analysis shows a statistically significant positive relationship between students’ PE and IU, where gender differences do not have any significant influence on their PE and IU. On the other hand, students who have experienced using Hello English for more than three months perceived the effect of Hello English on their communicative competence better than those who only use it less than three months. Besides, the experienced users also show a higher intention to use Hello English to learn English in the future.